Perancangan Aplikasi Presensi Dosen Realtime Dengan Metode Rapid Application Development (RAD) Menggunakan Fingerprint Berbasis Web - Darma Setiawan Putra; Ami Fauzijah (Jurnal Informatika: Jurnal Pengembangan IT, 2018)
The fingerprint is one of the biometric methods which is can be used in the education field. Attendance monitoring system using fingerprint will make the leaders easily to monitor the attendance of the lecturer and to make decisions. The fingerprint attendance is used to easy students detecting quickly and accurately the lecturer in the classroom. This system aims to provide the lecturer status information, entry or exit for teaching when every lecturer performs a fingerprint scanning. This study uses rapid application development (RAD) method to develop attendance system and involves the lecturer who have a teaching schedule in the current semester. To test the system, the lecturer was required to record the fingerprint in fingerprint machine. The result shows that the application of lecturer attendance in real time web-based can be a system provides the lecturers attendance information effectively and efficiently.